Education to increase the role of posyandu cadres in efforts to reduce stunting in Krajan Hamlet, Magelang - Athia Fidian; Ana Oftifyani; Ana Sri Rahayu; Nuzul Fatmawati; Yeni Rahmatin (Universitas Muhammadiyah Magelang, 2022)
In 2021, Magelang Regency will be one of the areas focusing on integrated stunting reduction initiatives, and it will be obliged to carry out stunting convergence actions. Education about stunting and how to prevent it is one of the activities that can help to minimize stunting. Because the role of posyandu cadres and mothers of toddlers is critical in attempts to reduce stunting rates, delivering stunting education to them is important. Village officials, posyandu cadres, and mothers of toddlers responded positively to this program and expressed their gratitude. Posyandu cadres gain knowledge and skills as stunting instructors as a result of this program, while mothers of toddlers educate about stunting and toddler nutrition.